2018
DOI: 10.5653/cerm.2018.45.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three-area laser-assisted zona thinning in 8-cell human embryos on pregnancy outcomes in vitro fertilization

Abstract: ObjectiveThis study conducted a preliminary examination of the effects of three-area laser-assisted zona thinning (LAZT) during the cleavage stage of embryo development on the hatching process in human in vitro fertilization-embryo transfer (IVF-ET) with subjects of advanced female age or frozen-thawed (FT) embryos.MethodsEight-cell stage embryos were treated with LAZT in three areas of the zona pellucida at 120° intervals. The control group was embryos without LAZT. Of the 72 consecutive fresh cycles and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The women were assigned into case group (n = 6) or control group (n = 6) according to patients' characteristics or response during previous cycles. IVF for women in both groups were performed as previously described [13]. For women in case group, acupuncture and moxibustion at points of guanyuan , zigong , zusanli , sanyinjiao , shenshu, and ciliao were also performed.…”
Section: Methodsmentioning
confidence: 99%
“…The women were assigned into case group (n = 6) or control group (n = 6) according to patients' characteristics or response during previous cycles. IVF for women in both groups were performed as previously described [13]. For women in case group, acupuncture and moxibustion at points of guanyuan , zigong , zusanli , sanyinjiao , shenshu, and ciliao were also performed.…”
Section: Methodsmentioning
confidence: 99%
“…The women were assigned to either the case group (n = 6) or the control group (n = 6) according to their characteristics or response during previous cycles. IVF was performed in women of both groups as previously described (Jeong et al 2018). Additionally, women in the case group underwent acupuncture at six points, i.e., Guanyuan (CV4), Zigong (EX-CA1), Zusanli (ST36), Sanyinjiao (SP6), Shenshu (BL23), and Ciliao (BL32).…”
Section: Patientsmentioning
confidence: 99%
“…Nonetheless, it is still unclear which method provides the best clinical outcomes despite numerous studies comparing the benefits of the two methods. Some studies suggest that T-LAH results in significantly better pregnancy outcomes in human 8-cell embryos compared to D-LAH [ 14 ]. Contrary to these findings, Shubhashree et al reported that zona thinning at the 8-cell stage in mouse embryos does not assist nor promote hatching in vitro [ 15 ] .…”
Section: Introductionmentioning
confidence: 99%